Etiological Structure of Community-Acquired Pneumonia in the period of COVID-19 epidemic - V. I. Sergevnin; M. V. Rozhkova; K. V. Ovchinnikov; E. Zh. Kuzovnikova (Эпидемиология и вакцинопрофилактика)
Relevance. The etiological structure of community-acquired pneumonia (CAP) with the widespread COVID-19 as backdrop is poorly studied. Aim. Comparative study of community-acquired pneumonia etiological structure in patients with and without a new coronavirus infection. Materials and methods. The etiology of CAP was estimated on the base of the results of bacteriological and molecular genetic studies of sputum samples and swabs from the posterior pharyngeal wall in 142 children and 190 adults in 1- 2 days from the moment they were hospitalized to two medical organizations of Perm in the period of 2021-2022 with a primary diagnosis of CAP. There were 131 negative and 11 positive for SARS-CoV-2 among pediatric patients. There were 84 negative and 106 – positive for SARS-CoV-2 among the adults. Results. It was found that in patients with CAP in the presence of COVID19, compared with SARS-CoV-2-negative patients, a more frequent isolation of K. pneumoniae, S. aureus, S. haemolyticus and H. influenzae DNA, as well as microbial associations of bacterial etiology. Conclusion. The results of the study can be used when choosing treatment tactics for combined infections.